Replication of British Rheumatoid Arthritis Susceptibility Loci in Two Unrelated Chinese Population Groups - Hua Li; Yonghe Hu; Tao Zhang; Yang Liu; Yantang Wang; Tai Yang; Minhui Li; Qiaoli Luo; Yu Cheng; Qiang Zou (Clinical and Developmental Immunology)
Previous genome-wide association study by WTCCC identified many susceptibility loci of common autoimmune diseases in British, including rheumatoid arthritis (RA). Because of the genetic heterogeneity of RA, it is necessary to replicate these susceptibility loci in other populations. Here, three SNPs with strong RA association signal in the British were analyzed in Han Chinese, and two SNPs (rs6457617 and rs11761231) were genotyped in the test cohort firstly. The rs6457617 was significantly associated with RA in the test cohort. The individuals bearing the homozygous genotype CC had 0.39-fold risk than these bearing the wild-type genotype TT (P=0.004, OR 0.39, [95% CI 0.21–0.74]). And the protective effect of allele C was confirmed in another validation cohort with 1514 samples (Pgenotye CC/TT=5.9 ×  10−10, OR 0.34, [95% CI 0.24–0.48]). The rs6457617 can be used as a tagSNP of HLA-DQA1*03 which encoded MHC-II α chain. Since MHC restriction is important for primary T-cells in positive selection and negative selection stages, MHC protein polymorphisms may be implicated in shaping the T-cell repertoire, including the emergence of a T-cell clone involved in the inflammatory arthritis.